Factors Influencing Military Personnel’s Resilience During Natural Disasters in Iran: A Qualitative Study - Ebadallah Shiri Malekabad; Simintaj Sharififar; Armin Zareian; Nasrin Jafari Golestan; Maryam Azizi; Seyed Amir Hosein Pishgooie (Health in Emergencies & Disasters Quarterly)
Background: Military personnel are exposed to various extreme stressors that may negatively impact their mental health and job performance. Resilience is essential in maintaining and enhancing mental health and performance in emergencies and disasters. This study aims to identify the factors influencing the resilience of military personnel during natural disasters. Materials and Methods: The present qualitative study was conducted on 24 military personnel with a history of involvement in emergency and disaster situations in Tehran, Kermanshah, Lorestan, and Golestan provinces, Iran, in 2024. The participants were selected using an available and targeted sampling method. Data were collected through semi-structured interviews, and the analysis was performed using a content analysis approach. Results: The results of the data analysis showed that the factors influencing the resilience of military personnel in emergencies amount to 18 factors classified into 7 main categories: individual characteristics, psychological characteristics, structural and organizational characteristics, stress-inducing agents, resources and supports, adaptive processes and positive outcomes. Conclusion: Military personnel in emergencies and disasters can achieve positive resilience outcomes during adaptation processes in cognitive and behavioral fields. The effective use of structural and organizational characteristics, resources and social support also increases the resilience of military personnel. The availability and presence of professional military personnel during major incidents help them cope with these conditions effectively and become more resilient.